Kemajuan Genetik dan Heritabilitas Karakter Agronomi Padi Beras Hitam pada Populasi F2 - Kristamtini, Kristamtini; Sutarno, Sutarno; Wiranti, Endang Wisnu; Widyayanti, Setyorini (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2016)
Black rice is a local rice variety with some advantages and weaknesses. The desirable character of black rice is its high anthocyanin content, while the weaknesses are late maturing, tall plant stature and low grain yield. Crosses were made between two parents aimed to recombine the superior traits. The effectiveness and efficiency of selection would be determined by the magnitude of the heritability of traits and the selection progress. This study was aimed to determine the heritability estimates in a broad sense and the genetic advance of agronomic characters of F2 generation, from crosses of local black rice and high yielding variety of white rice. The experiment was conducted in Padasan, Pakembinangun, Pakem, Sleman, Yogyakarta from January to May 2013. The F2 population derived from crosses of black rice x white rice, with the morphological traits of hairless black rice (S) crossed with Situbagendit (G) white rice, Cempo ireng (C) with Situbagendit (G) and Cempo ireng (C) with Inpari 6 (I). The F2 plants population were planted without replication. Genetic parameters estimated were calculated for broad sense heritability and genetic advance from selection. Results showed that the F2 population had high broad sense heritability estimates for all characters observed, including: plant height, flag leaf length, number of productive tillers, panicle length, number of filled grains per panicle, number of empty grains per panicle, maturity and rice color, in the three F2 populations obtained from crosses of S x G, C x G and C x I. Only the plant height of S x G cross had a medium broad sense heritability estimate. The large heritability estimates indicated that the respective character was controlled by genetic factor more than environmental ones. High genetic advance would be obtained in the flag leaf length, number of productive tillers, panicle length, number of filled grains/panicle, number of empty grains/panicle and rice color from S x G, C x G and C x I crosses. Genetic advance of plant height was medium (at S x G and C x I crosses) to high (C x G crosses). The maturity trait had low genetic advance on cross S x G; C x G; and Cx I. The high value of genetic advance of character would suggest that selection on the character’s appearance would be successful.